Creating new food microstructure: aerated hydro and aerogels - Samanci, S. (2020)
Aerated products are common in our daily life and bubbles in aerated products are either created by design or they are formed as a natural result of the processing steps and plays an important role in creating new structure, appearance, texture and giving a different mouthfeel. Aerogels are very light weight materials and can be made from various materials, such as polysaccharides, cellulose and proteins. The term “aerogel” was used to describe the gels that have been dried under supercritical conditions. However, in recent years the gels made by using other drying techniques, such as freeze drying, are also termed aerogels. In this research the main aim was to investigate the inclusion (aeration process), structuring and control of air as an active ingredient to generate a porous structure (air bubbles), which might be used to further control air cells in other formulations. A one-pot approach was used to create aerated hydrogel based on alginate ionic gelation in the presence of calcium carbonate (CaCO3) and glucono-delta lactone (GDL), cellulose derivatives including HPMC-K100M and K4M, MC-A4, non-starch polysaccharide locust bean gum (LBG) and whey protein isolate (WPI). It was recorded that the control of structuring was alginate gelation driven. However, adding MC/HPMC to alginate+ WPI hydrogels improved gel strength significantly with smaller air cells. Aerogels containing LBG had more intact air cells compared to other polymers with slow freezing while fast freezing provided more intact air cells in the final aerogels made of alginate, WPI and K100M.